Cryolithostratigraphy of the Middle Pleistocene to Holocene Deposits in the Dmitry Laptev Strait, Northern Yakutia - Tumskoy, Vladimir; Kuznetsova, Tatiana (Frontiers in Earth Science, 2022)
Oyogos Yar is the northernmost site of the continental coast of northern Yakutia. Until the beginning of the 21st century the frozen deposits within its range had been studied minimally. The present article discusses contemporary understandings of the deposition conditions, structure and stratigraphy of the Quaternary formations of Oyogos Yar obtained by the authors during their field research into the coasts of the Dmitry Laptev Strait.